Teaching Vocabulary To Young Learners: Combination Of Semantic Mapping And Bingo Game - Yoga Widiadnya, I Gusti Ngurah Bagus (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Students need to have many vocabularies in their mind in order to master four language skills in English namely listening, speaking, reading and writing. In addition, students should acquire number of words and they should know the meaning of the words then use them accurately. The vocabulary mastery would help students in developing their, understanding, and also enhancing the process of transferring information better. Teaching vocabulary is a challenge for teachers especially in teaching young learners. As the characteristics of young learner who love learning through playing, it is a need for the teacher to have an innovative strategy in teaching vocabulary. In addition, the combination of semantic mapping and bingo games will be the solution of the teaching vocabulary to young learners. This combination make the students learn words together with other students based on their background knowledge and review the vocabularies by implementing bingo games.